الاتساق النصي في لغة رواية "الربيع العاصف"للدكتور نجيب الكيلاني وأثره في بناء دلالة النص التفصيل بعد الإجمال نموذجا: Textual coherence, in language the novel of “al Rabī’ al ‘Āṣif” The significance of the text and its impact on the construction of “ALtafsil” after “Egmal” as a model - Mohamed Elsayed, Nashwa Mohamed; Ahmad Eldesoky, Ebrahim Mohammad (SIBAWAYH Arabic Language and Education, 2024)
لكل نص من النصوص ظروفه وسياقاته الخاصة التي على أساسها يختار آليات الاتساق النصي التي تناسبه وتعالج قضاياه، هذا وتكمن مشكلة هذا البحث في كيفية توضيح آلية التفصيل بعد الإجمال التي تشتمل عليها رواية الربيع العاصف وكيفية معالجتها وبيان أثرها في بناء دلالة نص رواية الربيع العاصف. ويهدف هذا البحث إلى وضع يد القارئ على المفهوم الصحيح للتفصيل بعد الإجمال وكذا مفهوم الاتساق النصي وكيف وظف الأديب الدكتور نجيب الكيلاني هذه الآلية المهمة من آليات الاتساق النصي في بناء دلالة الربيع العاصف من خلال الشواهد التطبيقية التي ذكرها في روايته. وقد اتبع البحث المنهج الوصفي التحليلي، فقام ببيان مفهوم آلية التفصيل بعد الإجمال ووصفها وصفا دقيقا ثم زاد ذلك وضوحا من خلال تحليل الشواهد التطبيقية التي اشتملت عليها رواية الربيع العاصف. هذا، وقد جاء البحث في أربعة مباحث يسبقها تمهيد وتعقبها خاتمة مشتملة على نتائج البحث ثم تعقبها المصادر والمراجع. أما المباحث فجاءت على النحو التالي: المبحث الأول: مفهوم الاتساق النصي. المبحث الثاني: مفهوم التفصيل بعد الإجمال. المبحث الثالث: قراءة في رواية الربيع العاصف. المبحث الرابع: من شواهد التفصيل بعد الإجمال في رواية الربيع العاصف. هذا وقد خلص البحث إلى عدد من النتائج أهمها: التفصيل بعد الإجمال علاقة من العلاقات الملحوظة المهمة في النص. - وظف الأديب الدكتور نجيب الكيلاني هذه الآلية المهمة من آليات الاتساق النصي أعني التفصيل بعد الإجمال في بناء دلالة الربيع العاصف وبدا ذلك واضحا من خلال الشواهد التطبيقية التي ذكرها في روايته. – يمتلك الأديب الدكتور نجيب الكيلاني أدوات الأديب المبدع التي تؤهله لمعالجة كثير من قضايا مجتمعه بعين الناقد البصير. Each text has its own circumstances and contexts on the basis of which it chooses the mechanisms of Textual coherence, that suit it and address its issues. The problem of this research lies in how to clarify the mechanism of Detail After Summarization included in the novel of “al Rabī’ al ‘Āṣif” And how to address it and explain its impact on building the significance of the text of the novel “al Rabī’ al ‘Āṣif”. This research aims to put the reader’s hand on the correct concept of Detail After Summarization. As well as the concept of textual coherence And how the writer Dr. Najib Al-Kilani employed this important mechanism of textual coherence in building the significance of the novel “al Rabī’ al ‘Āṣif”. Through the applied models that he mentioned in his novel. The research followed the descriptive analytical approach, so he explained the concept of the mechanism of Detail After Summarization and described it accurately. This was then further clarified by analyzing the the applied models included in the novel “al Rabī’ al ‘Āṣif”. The research came in four sections, preceded by a preface and followed by a conclusion that includes the results of the research, then followed by sources and references As for the detectives, they came as follows The first section: the concept of textual coherence. The second section: the concept of Detail After Summarization The third section: reading in the novel of “al Rabī’ al ‘Āṣif”. The fourth topic: from the models of Detail After Summarization in the novel of “al Rabī’ al ‘Āṣif”. The research concluded a number of results, the most important of which are. 1-. Detail After Summarization is one of the important notable relationships in the text. 2 The writer Dr. Najib Al-Kilani employed the mechanism of Detail After Summarization, which is one of the most important mechanisms of textual coherence in building the significance of “al Rabī’ al ‘Āṣif”. This was evident through the empirical models he mentioned in his novel. 3- The writer Dr. Najib Al-Kilani has the tools of the creative writer that qualify him to address many of the issues of his society with the eye of the insightful critic. Keywords: Detail, Summarization, coherence, text, significance, novel